Ferroptosis: A new therapeutic target for bladder cancer - Zeng, Fan; Lan, Yunping; Wang, Ning; Huang, Xiaobo; Zhou, Qiao; Wang, Yi (Frontiers in Pharmacology, 2022)
Bladder cancer (BC) is the most frequent type of urinary system cancer. The prognosis of BC is poor due to high metastasis rates and multidrug resistance. Hence, development of novel therapies targeting BC cell death is urgently needed. As a novel cell death type with strong antitumor potential, ferroptosis has been investigated by many groups for its potential in BC treatment. As an iron-dependent cell death process, ferroptosis is characterized by excessive oxidative phospholipids. The molecular mechanisms of ferroptosis include iron overload and the system Xc-GSH-GPX4 signaling pathway. A recent study revealed that ferroptosis is involved in the metastasis, treatment, and prognosis of BC. Herein, in this review, we comprehensively summarize the mechanism of ferroptosis, address newly identified targets involved in ferroptosis, and discuss the potential of new clinical therapies targeting ferroptosis in BC.